PROGRAM “E-FUNTASTIC ( ENGLISH FUN AND FANTASTIC) UNTUK SISWA TAMAN KANAK-KANAK DESA GAPURO SUKOLILO GRESIK - Sriwulandari, Novi; Syafii, Mochamad; Dewi, Risma Kartika; Yaqin, Muhammad Ainul; Sundari, Sri (Universitas Muhammadiyah Gresik, 2023)
Gapuro Sukolilo Village Kindergarten is one of the schools owned by the village that has the potential for development in the field of education. In improving the quality in the field of education, TK GapuroSukolilo makes an English extracurricular activity for its students. However, based on the results of observations and interviews, it was found that this school had difficulties in assisting in learning English where there were no English teachers for their students and how to teach English to students aged 3-5 years. To deal with this problem, the Community Service Team (KKN) team -05 GapuroSukolilo Village has developed a program called E-Funtastic, namely English Fun and Fantastic. This program is a mentoring program to learn English for students in groups A, B and play groups (KB) using the Active Joyful Based Learning (AJBL) method. To carry out this program, a preparation stage is carried out including the preparation of teaching materials and learning media. Second, the implementation stage of the work program where this program was carried out for three days at the GapuroSukolilo Kindergarten. The last is the evaluation of the results. The results obtained from this activity are an English learning mentoring program in the form of a service that provides solutions and real contributions to GapuroSukolilo Kindergarten where teachers experience difficulties in teaching English to their students and in the kindergarten there are no teaching staff to assist learning. English. So the E-Funtastic program is very useful for teachers and students in assisting student learning, especially in terms of learning English.